The HER family as therapeutic targets in colorectal cancer. (June 2022) - Ye, Peng; Wang, Yiran; Li, Ruiqi; Chen, Wanlu; Wan, Lu; Cai, Peiling
Abstract: The human epidermal growth factor receptor (HER, ErbB) family has four members, epidermal growth factor receptor (EGFR), HER2, HER3, and HER4. Although distinct in ligands and functions, all of the HER family members are receptor tyrosine kinases playing important roles in the pathogenesis of cancers. In the era of precision medicine, the HER family is one of the most important and successful cancer therapeutic targets, hallmarked by the approval of anti-EGFR therapies for the treatment of colorectal cancer and non-small cell lung cancer, and anti-HER2 therapies for the treatment of breast cancer and gastric cancer. This review briefly discusses how HER family members were discovered, their functions and roles in cancer, and most importantly, the developmental history and recent updates of therapies targeting HER family members, with colorectal cancer as a focus. We also discussed the patient selection and drug resistance to anti-EGFR therapies in the treatment of colorectal cancer. Graphical Abstract: ga1 Highlights: Discovery and biology of the HER family were summarized. Developmental history of anti-HER treatments in colorectal cancer was summarized. Recent progress of HER-targeted therapies in colorectal cancer was summarized. Patient selection of anti-EGFR therapies in colorectal cancer was summarized. Drug resistance of anti-EGFR therapies in colorectal cancer was summarized.